Neisseria gonorrhoeae and Chlamydia trachomatis infection in HIV-1-infected women taking antiretroviral therapy: a prospective cohort study from Burkina Faso. (13th December 2013) - Low, Andrea J; Konate, Issouf; Nagot, Nicolas; Weiss, Helen A; Mabey, David; Segondy, Michel; Vickerman, Peter; Meda, Nicolas; van de Perre, Philippe; Mayaud, Philippe; ,
Abstract : Objectives: Neisseria gonorrhoeae (NG) and Chlamydia trachomatis (CT) are common sexually transmitted infections (STI). We assessed the cumulative risk of NG and CT in a cohort of HIV-1-infected high-risk women taking antiretrovirals over 4 years in Burkina Faso. Methods: Between March 2007 and February 2011, participants were followed every 3–6 months. At each visit, participants underwent a gynaecological examination with collection of cervical and vaginal swabs. Random-effects logistic regression models were used to analyse associations of NG and CT infection with behavioural and biological factors. Results: 172 women had samples tested for NG and CT during the study period, in a total of 1135 visits. NG was detected in 6.4% of women (11/172, 95% CI 2.7 to 10.1) at a rate of 2.76 cases (95% CI 1.53 to 4.99) per 100 person-years. CT was detected in 1.7% (3/172, 95% CI 0 to 3.7) of women at a rate of 0.75 cases (95% CI 0.24 to 2.34) per 100 person-years. The majority of women were asymptomatic (9/14). In the multivariable model, the presence of NG or CT was associated with tobacco use (aOR=11.85, 95% CI 1.13 to 124.17), and concurrent genital HIV-1 RNA shedding (aOR=4.78, 95% CI 1.17 to 19.46). Higher levels of education (aOR=0.17, 95% CI 0.03 to 0.92), and age greater than 35 years (aOR=0.07, 95% CI 0.01 to 0.92) were associated with lower odds of infection. Conclusions: The risk of NG or CT infection remains low among high-risk women in Bobo-Dioulasso. This provides some evidence that antiretroviral use does not contribute to behavioural disinhibition. The asymptomatic nature of most infections underscores the need for regular screening and treatment of STIs in core groups.